1999
DOI: 10.1093/ndt/14.10.2427
|View full text |Cite
|
Sign up to set email alerts
|

Altered abdominal fat distribution and its association with the serum lipid profile in non-diabetic haemodialysis patients

Abstract: These data indicate that haemodialysis patients exhibited a visceral fat accumulation irrespective of BMI, and this shift of abdominal adiposity might be associated with disturbance of the serum lipid profile in non-diabetic haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
2
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 30 publications
4
52
2
3
Order By: Relevance
“…HOMA-IR, homeostasis model assessment-insulin resistance index; CRP, C-reactive protein; HD, hemodialysis; SFA, subcutaneous fat area; RLP, remnant-like particle; VFA, visceral fat area; HDL, highdensity lipoprotein. some differences between our results and the report by Odamaki et al (21). They failed to show that both VFA and SFA contribute to insulin resistance in HD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…HOMA-IR, homeostasis model assessment-insulin resistance index; CRP, C-reactive protein; HD, hemodialysis; SFA, subcutaneous fat area; RLP, remnant-like particle; VFA, visceral fat area; HDL, highdensity lipoprotein. some differences between our results and the report by Odamaki et al (21). They failed to show that both VFA and SFA contribute to insulin resistance in HD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…22 Odamaki et al demonstrated that 92 patients without diabetes who were treated with hemodialysis had significantly increased visceral fat and decreased subcutaneous fat compared with control subjects of similar BMI. 23 Furthermore, an experimental study also showed a shift of subcutaneous fat to ectopic fat in uninephrectomized rats as a renal dysfunction model. 24 Some recent studies investigated the impact of EAT accumulation on renal function and future cardiovascular events in patients with CKD.…”
Section: Discussionmentioning
confidence: 98%
“…Altered fat distribution is proposed to be a key contributory factor to atherosclerosis progression in patients with CKD of any degree. 21- 23 Kim et al found a significant reverse correlation between visceral fat volume and eGFR in 929 patients with type 2 diabetes mellitus. 21 Lamacchia et al showed increased para-and perirenal fat thickness in patients with CKD compared with those with preserved renal function on echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and nephron reduction can promote a decrease in glomerular filtration rate and an increase in proteinuria (119). Nondiabetic patients on hemodialysis presented with decreased body fat area and subcutaneous fat mass but increased visceral fat and altered serum lipid profiles, suggesting that reduced kidney function leads to fat redistribution and/or altered adipocyte differentiation (111). This underscores the importance of the kidney for lipid homeostasis.…”
Section: Association Of the Western-style Diet And Metabolic Disease mentioning
confidence: 96%